2006
DOI: 10.1016/j.febslet.2006.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic induction of human visfatin gene is directly mediated by hypoxia‐inducible factor‐1

Abstract: Visfatin has been originally identified as a growth factor for early stage B cells and recently known as an adipokine. Here, we report that hypoxia induces the visfatin mRNA and protein levels in MCF7 breast cancer cells. We also demonstrate that induction of visfatin gene is regulated by hypoxia-inducible factor-1a (HIF-1a). Moreover, 50 -flanking promoter region of human visfatin gene contains two functional HIF responsive elements (HREs), activating the expression of visfatin. Mutation of these HREs in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 42 publications
4
83
0
2
Order By: Relevance
“…These acute phase proteins are released by the liver suggesting a hepatic response to inflammation rather than a systemic inflammatory process as indicated by the pattern of cytokine release. In agreement with previous results performed in 3T3-L1 adipocytes and MCF-7 cells [60,61], we found that gene expression of NAMPT in PBC in vivo, was positively correlated with HIF1-« mRNA expression in humans, a wellcharacterized key regulator of the adaptive response to low oxygen tension present in the obesity-associated inflammation state [34,62,63]. Taken together, these associations may contribute to the role of NAMPT in the obesity-associated inflammatory state, which takes place in the obesity-related cardiovascular derangements.…”
Section: Discussionsupporting
confidence: 83%
“…These acute phase proteins are released by the liver suggesting a hepatic response to inflammation rather than a systemic inflammatory process as indicated by the pattern of cytokine release. In agreement with previous results performed in 3T3-L1 adipocytes and MCF-7 cells [60,61], we found that gene expression of NAMPT in PBC in vivo, was positively correlated with HIF1-« mRNA expression in humans, a wellcharacterized key regulator of the adaptive response to low oxygen tension present in the obesity-associated inflammation state [34,62,63]. Taken together, these associations may contribute to the role of NAMPT in the obesity-associated inflammatory state, which takes place in the obesity-related cardiovascular derangements.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, PBEF itself induces its own production, indicating the existence of a positive feedback-regulating mechanism. Expression and upregulation of human PBEF has previously been documented in neutrophils by IL-1␤ and LPS, in amniotic cells by TNF␣, in monocytic cells by nitric oxide, in adipocytes by hypoxia, and in RASFs by IL-6 transsignaling (10,11,13,(21)(22)(23). Taken together, these data show that signaling pathways of the innate immune system have a strong regulatory effect on the expression of PBEF in a variety of cell types.…”
Section: Discussionsupporting
confidence: 62%
“…Hypoxia increases testosterone release in the mouse TM3 cell line mediated by increased VEGFA production (Hwang et al 2007). Interestingly, hypoxia leads to an increase in NAMPT gene expression in adipocytes and in a breast cancer cell line (Bae et al 2006, Segawa et al 2006. Collectively, it appears that NAMPT can play a major role in testicular cellular metabolism, vascularization, and in Sertoli cell and Leydig cell functions.…”
Section: Discussionmentioning
confidence: 94%